Repeatability and Reproducibility Assessment of the Apparent Diffusion Coefficient in the Prostate: A Trial of the ECOG‐ACRIN Research Group (ACRIN 6701). Issue 3 (10th February 2022) - Boss, Michael A.; Snyder, Bradley S.; Kim, Eunhee; Flamini, Dena; Englander, Sarah; Sundaram, Karthik M.; Gumpeni, Naveen; Palmer, Suzanne L.; Choi, Haesun; Froemming, Adam T.; Persigehl, Thorsten; Davenport, Matthew S.; et al.
Abstract : Background: Uncertainty regarding the reproducibility of the apparent diffusion coefficient (ADC) hampers the use of quantitative diffusion‐weighted imaging (DWI) in evaluation of the prostate with magnetic resonance imaging MRI. The quantitative imaging biomarkers alliance (QIBA) profile for quantitative DWI claims a within‐subject coefficient of variation (wCV) for prostate lesion ADC of 0.17. Improved understanding of ADC reproducibility would aid the use of quantitative diffusion in prostate MRI evaluation. Purpose: Evaluation of the repeatability (same‐day) and reproducibility (multi‐day) of whole‐prostate and focal‐lesion ADC assessment in a multi‐site setting. Study Type: Prospective multi‐institutional. Subjects: Twenty‐nine males, ages 53 to 80 (median 63) years, following diagnosis of prostate cancer, 10 with focal lesions. Field Strength/Sequence: 3T, single‐shot spin‐echo diffusion‐weighted echo‐planar sequence with four b ‐values. Assessment: Sites qualified for the study using an ice‐water phantom with known ADC. Readers performed DWI analyses at visit 1 ("V1") and visit 2 ("V2, " 2–14 days after V1), where V2 comprised scans before ("V2pre") and after ("V2post") a "coffee‐break" interval with subject removal and repositioning. A single reader segmented the whole prostate. Two readers separately placed region‐of‐interests for focal lesions. Statistical Tests: Reproducibility and repeatability coefficients for whole prostate and focal lesions derived from median pixel ADC. We estimated the wCV and 95% confidence interval using a variance stabilizing transformation and assessed interreader reliability of focal lesion ADC using the intraclass correlation coefficient (ICC). Results: The ADC biases from b 0 – b 600 and b 0 – b 800 phantom scans averaged 1.32% and 1.44%, respectively; mean b ‐value dependence was 0.188%. Repeatability and reproducibility of whole prostate median pixel ADC both yielded wCVs of 0.033 ( N = 29). In 10 subjects with an evaluable focal lesion, the individual reader wCVs were 0.148 and 0.074 (repeatability) and 0.137 and 0.078 (reproducibility). All time points demonstrated good to excellent interreader reliability for focal lesion ADC (ICCV1 = 0.89; ICCV2pre = 0.76; ICCV2post = 0.94). Data Conclusion: This study met the QIBA claim for prostate ADC. Test–retest repeatability and multi‐day reproducibility were largely equivalent. Interreader reliability for focal lesion ADC was high across time points. Level of Evidence: 1 Technical Efficacy: Stage 2 TOC Category: Pelvis